Expression of Concern Notice: Wearable Sports Smart Glasses Real-time Monitoring and Feedback Mechanism in Physical Education - Zhang, Zhongchen; Wang, Xiaomei (EAI Endorsed Transactions on Pervasive Health and Technology, 2026)
We, the publisher, are issuing an expression of concern about Zhongchen Zhang, Xiaomei Wang (2024) Wearable Sports Smart Glasses Real-time Monitoring and Feedback Mechanism in Physical Education.https://doi.org/10.4108/eetpht.10.5531There is a concern over the integrity of the peer review review process and suspected manipulation of the editorial process. The investigation is ongoing and we advise scholars to exercise caution when referencing this manuscript.